2004
DOI: 10.1242/jcs.01193
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyltransferase inhibitors disrupt EGF receptor traffic through modulation of the RhoB GTPase

Abstract: The Rho family of small GTPases play a pivotal role in the dynamic regulation of the actin cytoskeleton. Recent studies have suggested that these signalling proteins also have wide-ranging functions in membrane trafficking pathways. The Rho family member RhoB was shown to localise to vesicles of the endocytic compartment, suggesting a potential function in regulation of endocytic traffic. In keeping with this, we have previously shown that expression of active RhoB causes a delay in the intracellular trafficki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
108
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 62 publications
13
108
1
1
Order By: Relevance
“…It also has a unique pattern of cellular distribution. It has been localized to specialized membrane compartments including the Golgi, endosomal vesicles, and the multivesicular body (MVB) [3,4]. This localization is consistent with several studies which suggest an important role for RhoB in endosome-mediated trafficking of growth factor receptors [4,5].…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…It also has a unique pattern of cellular distribution. It has been localized to specialized membrane compartments including the Golgi, endosomal vesicles, and the multivesicular body (MVB) [3,4]. This localization is consistent with several studies which suggest an important role for RhoB in endosome-mediated trafficking of growth factor receptors [4,5].…”
Section: Introductionsupporting
confidence: 87%
“…RhoB has been localized to the limiting membrane of the mammalian MVB [4], while Bcr interacts with subunits of the ESCRT sorting complexes that are found on the same membrane [25,33]. TSG101 is a subunit of the ESCRT complex that has been shown to directly interact with Bcr [25].…”
Section: Rhob-dependent Activation Of Nf-κb By Tsg101mentioning
confidence: 99%
“…3, C and D). It is important to note that farnesyltransferase inhibitors may increase the production of geranylgeranylated proteins, presumably by shunting excess FPP to GGPP (56). This suggests that farnesyltransferase inhibitors may not solely act by decreasing farnesylated proteins, but instead they may also change the balance in favor of geranylgeranylated proteins.…”
Section: Lovastatin-enhanced Efferocytosis Is Dependent On Prenylationmentioning
confidence: 99%
“…Recent works of Wherlock 28 has demonstrated that, in HeLa cells, RhoB is localized in the plasma membrane and vesicles. FTI treatment of these cells caused a loss of RhoB plasma membrane staining, suggesting that RhoB-F may be localized to the plasma membrane, while RhoB-GG resides in the endocytic compartment.…”
Section: Rhob-f Inhibits Radiation-induced Mitotic Cell Death and Cenmentioning
confidence: 99%